Influence of Motivation and Compensation on Employee Performance through Job Satisfaction at PT Biofarma (Persero) - Asep Hamdani; R. Ervin Agung Priambodo (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Employee performance is an important thing that needs to be considered because it has an important role in the success of a company. Employee performance is not only influenced by individual abilities, but also by motivational factors, compensation and job satisfaction. This research aims to analyze the direct influence of motivation, compensation and job satisfaction on employee performance at PT Biofarma (Persero), the influence of motivation on employee performance at PT Biofarma (Persero) through job satisfaction, and the influence of compensation on employee performance at PT Biofarma (Persero) through job satisfaction. The type of research used is quantitative research, with a sample size of 202 respondents. Data collection uses a questionnaire distributed via Google Form. The data processing method uses path analysis with SPSS 22.0 and Sobel Test. The research results show; motivation has a significant effect on employee performance, compensation has no significant effect on employee performance, motivation has a significant effect on employee performance through job satisfaction, compensation has a significant effect on employee performance through job satisfaction, and job satisfaction has a significant effect on employee performance at PT Biofarma (Persero)